PELUANG PELUANG DAN TANTANGAN: EKSISTENSI PASAR TRADISIONAL DAN PASAR MODERN DI ERA GLOBALISASI : Pasar tradisional, Pasar modern, Globalisasi - Zahrotun Niswah (Program Studi Hukum Tata Negara dan diterbitkan oleh Program Studi Hukum Tata Negara dan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2024)
The market is a place where sellers and buyers meet to carry out transactions and fulfill daily needs. As time goes by, the types of markets in Indonesia do not only contain traditional markets but there are also modern markets. Traditional markets and modern markets are proof that our country is increasingly developing. This development is influenced by the phenomenon of globalization in several countries, making it easier for traders to invest. This investment can take the form of building supermarkets, hypermarkets, etc. as modern markets. The emergence of this development will certainly give rise to new challenges in the world of trade. Apart from the emergence of challenges, of course there will also be opportunities that can be obtained from traditional markets and modern markets. It cannot be denied that in this era of globalization, the development of communication technology is also growing, where someone can shop for whatever goods they want just via cellphone, they can even make payments online. However, there are still many people who are still unable to move away from habits that have been their custom since ancient times, such as shopping at the market (not through online media). Surveys have proven that the distance between traditional markets and modern markets is not has a lot of influence in the world of commerce. Because each trader has their own way of promoting the goods they sell. Either from social media or from reviews from customers who have been to the merchant's location. Therefore, the researcher will discuss the challenges and opportunities that traders will get in traditional markets and modern markets.